Aspek Hukum terhadap Bisnis Jual-Beli Sex Toys di Indonesia - Devi Wiranti Napitupulu; Hery Firmansyah (Departement of Mathematics Education, 2022)
In line with the rapid development of technology, goods will increase and new innovations from foreign countries will emerge. Sex toys are tools in sexual relations that are useful for self-pleasure. The users of these sex aids come from all age groups, from teenagers to the elderly, even sex toys are very easy to find because there are many selling them on social media. These objects have positive and negative impacts on the younger generation, especially on minors. The research method used is normative research. The results of the study show that actually the rules regarding sex toys do not have specific rules, but the relationship between sex toys and other laws has a relationship, namely the Criminal Code, Law no. 44 of 2008 concerning Pornography, Law No. 17 of 2006 concerning Customs. With this there must be legal certainty from the government so that the sale of sex toys is not misused by the public and does not raise doubts for sellers and buyers of sex toys.